Kebencanaan dalam Novel Anak-Anak Pangaro Karya Nun Urnoto El-Banbary: Kajian Ekokritik Sastra - Nur Khayatun Khayatun; Sony Sukmawan (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2024)
This research aims to analyze the forms of natural disasters, efforts to overcome natural disasters, and the impact of the migitation efforts contained in the novel Anak-Anak Pangaro using literary ecocritical studies. This research was conducted using a qualitative descriptive research method with a content analysis research design. The data sources used are excerpts of dialogue and narration contined in the novel Anak-Anak Pangaro by Nun Urnoto El-Banbary. The data collection technique used is the cultural document observation technique. Meanwhile, the data analysis technique used includes four stages, namely data reduction, data presentation, data verification, and conclusion drawing. Results of this study are; (1) The form of natural disasters contained in the novel Anak-Anak Pangaro in the form of water drought and abrasion; (2) Natural disaster management efforts contained in the novel Anak-Anak Pangaro in te form of reforestation, clean water contribution, and nasuha repentance; (3) The impact of disaster management efforts of the changes in the religious system of the Giliraja people and the increasing attitude of caring for nature in the Giliraja people.